Nurturing sustainable communities in affordable housing programmes and policy in Malaysia - Mat Isa, Norlaili; Daud, Mahyuddin (IIUM Press, 2023)
A healthy community requires the fulfilment of basic needs, such as accommodation, food, financial, environmental sustainability, and social justice. In this regard, the Malaysian Government launched the National Community Policy, among others, to promote access to a healthy lifestyle. Despite the existence of such a policy, there exists issues and challenges in providing adequate housing in Malaysia, which affects access to a healthy lifestyle in the community. Literature and content research on different platforms from previous reports, articles and mass media provide an overview of the need for sports community policy as a sustainable development objective for affordable housing programmes. The research will be restricted to the international and local policies applicable in recognising the right to a healthy community. This paper concludes that sports facilities should be assimilated into affordable housing programmes in fostering sustainability.